IgE screening in 1701 newborn infants and the development of atopic disease during infancy. Issue 5 (May 1982) - Croner, S; Kjellman, N I; Eriksson, B; Roth, A
Abstract : IgE screening was done using the Phadebas IgE PRIST technique on the cord blood of 1701 newborn infants. Of these 8.3% developed obvious or probable atopic disease, predominantly atopic dermatitis and bronchial asthma, during the first 18 months of life. Of infants with a family history of atopic disease 10.5% developed such illness; the corresponding figure for infants with an initially high IgE concentration was 70%. Atopic disease developed in 73% of infants with a high IgE concentration in cord blood and a family history, but in only 3% of infants with a low IgE and no family history. A high IgE concentration in cord blood was associated with a high IgE and a positive radioallergosorbent test at between ages 18 and 24 months more often than was a low initial IgE level, indicating that in man as in animals there are high and low IgE responders already genetically coded at birth. IgE screening in cord blood is recommended if there is obvious atopy in both parents or if severe atopic disease if present in a sibling or in one parent.